Laplace–Elzaki Transform and its Properties with Applications to Integral and Partial Differential Equations - Shaikh Al-Sook, Safaa Adnan; Amer, Mohammad Mahmud (Journal of natural sciences, life and applied sciences, 2019)
Laplace-Elzaki transform (LET) as a double integral transform of a function  of two variables was presented to solve some integral and partial differential equations. Main properties and theorems were proved. The convolution of two function  and  and the convolution theorem were discussed. The integral and partial differential equations were turned to algebraic ones by using (LET) and its properties. The results showed that the Laplace-Elzaki transform was more efficient and useful to handle such these kinds of equations.
Keywords: Laplace-Zaki transform; Laplace transform; Zaki transform; convolution (folding); integral and partial differential equations